2022
DOI: 10.1021/acs.molpharmaceut.2c00571
|View full text |Cite
|
Sign up to set email alerts
|

Development of In Silico Models for Predicting Potential Time-Dependent Inhibitors of Cytochrome P450 3A4

Abstract: Cytochrome P450 3A4 (CYP3A4) is one of the major drug metabolizing enzymes in the human body and metabolizes ∼30–50% of clinically used drugs. Inhibition of CYP3A4 must always be considered in the development of new drugs. Time-dependent inhibition (TDI) is an important P450 inhibition type that could cause undesired drug–drug interactions. Therefore, identification of CYP3A4 TDI by a rapid convenient way is of great importance to any new drug discovery effort. Here, we report the development of in silico clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…To clarify the mechanism of interaction, we first performed IC 50 shift experiments to determine whether the inhibition was time dependent (Xu et al, 2023). The results showed that the ratio of IC 50 (-NADPH) to IC 50 (+NADPH) of telmisartan and carvedilol in RLM was less than 1.5, indicating that the inhibition was not time dependent (Supplementary Figure S4).…”
Section: Telmisartan and Carvedilol Inhibit The Metabolism Of Aumoler...mentioning
confidence: 99%
“…To clarify the mechanism of interaction, we first performed IC 50 shift experiments to determine whether the inhibition was time dependent (Xu et al, 2023). The results showed that the ratio of IC 50 (-NADPH) to IC 50 (+NADPH) of telmisartan and carvedilol in RLM was less than 1.5, indicating that the inhibition was not time dependent (Supplementary Figure S4).…”
Section: Telmisartan and Carvedilol Inhibit The Metabolism Of Aumoler...mentioning
confidence: 99%
“…To clarify the type of interaction, we first conducted IC 50 shift experiments to determine whether the inhibition was time-dependent (Xu et al, 2023). The results showed that the IC 50 (−NADPH) to IC 50 (+NADPH) ratio of nimodipine, amlodipine, and felodipine in the rat liver was less than 1.5, indicating that the inhibition was not time-dependent (Supplementary Figure 3).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In their investigations, models were built with a highly imbalanced TDI data set with 7914 molecules and only 580 TDI positive data. 24 In this work, deep learning models were developed for the prediction of CYP3A4 TDI and compared to experimental variability with the aim of comparing their quality for decisionmaking in drug design. Realistic evaluation settings were applied, where the generalization ability of the models was estimated by temporal or prospective validations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tang et al reported a benchmark of ML methods and molecular features for categorical TDI CYP3A4 categorical predictions. In their investigations, models were built with a highly imbalanced TDI data set with 7914 molecules and only 580 TDI positive data …”
Section: Introductionmentioning
confidence: 99%